Reform to the Colombian justice administration from the perspective of a judicial operator - Torres-Calderón, Leonardo Augusto (Universidad Pedagógica y Tecnológica de Colombia, 2014)
This article written by the President of the Administrative Court of Cundinamarca offers a very authoritative perspective on the current crisis of  justice in Colombia, through a series of formulas that were presented at a symposium organized by the UPTC in Bogotá jointly with other universities and lawyers associations. The judicial strike called by judicial branch unions is a true demonstration of the crisis affecting the sector, with huge wage gaps and congestion that demands urgent action so that, the most vulnerable branch of public power can be appropriately treated.